Hubungan Antara Culture Shock dengan Tingkat Stres Kerja - Clarita Dea Angella; Dyah Wiji Puspita Sari; Retno Issroviatiningrum (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Nurse is power vulnerable health​ experiencing Culture Shock, namely difficulty adapt with environment Work new that has difference culture. A preliminary study was conducted at the Sultan Agung Islamic Hospital in Semarang on 12 nurses. show that 89.85% experienced Culture Shock. Of them, 71.05% faced stress Work light, 78.95% stress Work moderate , and 85.53% stressed Work weight . This result indicates the need study more carry on For evaluate connection between Culture Shock and level stress Work nurse , so that step intervention can formulated for quality service health. Analyze connection between Culture Shock and level stress Work nurse at Sultan Agung Islamic Hospital, Semarang. Study quantitative with cross-sectional design, conducted on 95 nurses at the Sultan Agung Islamic Hospital in Semarang using total sampling technique . Data collected use valid and reliable questionnaire , with analysis using the Chi-square. Based on results study This show that from 95 nurses implementers at the Sultan Agung Islamic Hospital in Semarang, as many as 20,0% experienced Culture Shock in the category less , 33,7% category enough , and 46,3% category good . Meanwhile that , level stress Work shows 56,8% in category light , 33,7% category medium , and 9,5% category heavy. Study This conclude that there is connection significant between Culture Shock and level stress Work nurses at Sultan Agung Islamic Hospital Semarang (p = 0.000).